Governing India : issues concerning public policy, institutions, and administration - Dwivedi, O. P.; Jain, B. R.; Vajpeyi, Dhirendra K.; Chaturvedi, Triloki Nath. (Delhi : B.R. Pub. Corp., 1998)
Contributed articles.
"Essays in honour of Shri T.N. Chatuvedi, Padma Vibhushan, M.P." -- Added t.p.
Includes bibliographical references and index.
Keywords: Public administration -- India; Civil service -- India; India -- Politics and government -- 1947-